Gender in French Freemasonry, From the Eighteenth Century Until Today - Révauger, Cécile (2013)
Since the origins of Speculative Freemasonry, the relationship between this institution and women has been controversial, and remains that way after three centuries of Masonic existence. In this article, the history of this relationship in France, from the eighteenth century to the present day is updated. France is an important country in which to analyze this topic, since it has caused a number of debates and diverse projects to incorporate women into the Symbolism.